Waste Management Through The Reduce, Reuse And Recycle Approach At Gunung Sari Market West Lombok District - nasruddin, nasruddin; Iswan; Suryaningsih; Nurwahidah (Journal Ilmiah Rinjani : Media Informasi Ilmiah Universitas Gunung Rinjani, 2024)
Waste management at Gunung Sari Market is a very important requirement for the cleanliness of Gunung Sari Market itself. In facing current challenges, the existence of a clean environment and increasingly stringent regulations from the Government, the Gunung Sari market needs to have a good waste management pattern based on waste generation and composition. The aim of this research is to find out how waste is managed at Gunung Sari Market, West Lombok. This research method is descriptive qualitative with data collection tools namely observation, interviews, surveys. The results of this research show that waste management at Gunung Sari Market using the 3R Approach (Reduce, Reuse, Recycle) with grouping based on the type of waste, can reduce waste generation and optimize the use of resources, through reducing waste at the source, reusing materials that can be recycled recycling, and efficient recycling processes, thereby reducing environmental impacts and generating sustainable economic benefits. Management of the Gunung Sari Market using the 3R approach must start with waste containerization, this must be provided by the Gunung Sari Market Management, namely 3 liters, placed in each aisle and the type of waste differentiated namely organic and inorganic waste. With a volume of organic waste of 11.2 L/day with a composted waste capacity of 8.8 L/day, the number of composter drums that must be prepared is 4. Meanwhile, waste residue has a volume of 3 L/day with a storage capacity of 21 liters with an organic waste storage area of ​​2 m3 with a length of 2 m, a width of 1 m and a height of 1 m. The suggestion in this research is that it is hoped that future researchers will carry out waste container planning to make it easier to calculate the amount of each waste source so that waste management using the 3 R's can be easily carried out. Keywords: Waste Management, Reduce, Reuse and Recycle Approach.